Role of Electromyography in Dental Research: A Review - SR Patil; BR Doni; CH Patil; SH Nawab; M Khursheed Alam (Islamic Azad University, 2023)
Background and Aim: The purpose of this review was to provide an overview of the use of electromyography (EMG) in dentistry over the past several years, as well as related research. EMG is a sophisticated technique used to detect and analyze muscle activity. EMG was primarily utilized in medical sciences in the past, but it is now widely utilized in both the medical and dental fields.   Materials and Methods: Electronic search was conducted in EMBASE, PubMed, Scopus, Web of Science, and Google Scholar to find all clinical studies regarding applications of EMG in dentistry. Results: This review included 31 papers in all. According to the results, neuromuscular activity may be recorded using EMG for both diagnostic and therapeutic purposes. It could be used in dentistry to evaluate parafunctional habits such as clenching and bruxism as well as muscle activation during actions like chewing and biting. In recent years, the use of EMG in treatment of temporomandibular joint (TMJ) and myofascial pain disorders has significantly increased. Conclusion: EMG has a variety of applications in dentistry for monitoring, diagnostic, and therapeutic purposes.